"Money Is Your Government": Refugees, Mobility, and Unstable Documents in Kenya's Operation Usalama Watch. (September 2016) - Balakian, Sophia
Abstract: During a 2014 security operation in Kenya known as Operation Usalama Watch, Somali refugees spoke of money as their only valid ID, knowing that only cash, in contrast to identity documents, would be accepted by police and military. The article argues that such extortion should not be interpreted uncategorically as an example of refugees' exclusion from state-derived citizenship rights. Rather, by paying bribes to resist forced removal from Nairobi, Somali refugees constructed a global diasporan identity tied to free flows of capital. By using money as a substitute for identity documents, refugees appealed to a notion of rights untethered to the state. At the same time, by speaking of money as their government, they articulated a critique against a political system that excluded them. Résumé: En 2014, au cours d'une opération de sécurité au Kenya nommée Opération Usalama Watch, les réfugiés somaliens ont parlé de l'argent comme de leur seule valide identité, sachant que seule l'argent liquide, contrairement aux documents d'identité, serait acceptée par la police et les militaires. L'article soutient que cette extorsion de fonds ne doit pas être interprétée d'une façon catégorique comme un exemple de l'exclusion des réfugiés aux droits de citoyenneté provenant de l'État. Au contraire, en payant des pots de vin pour résister au retrait forcé de Nairobi, les réfugiés somaliens ont construit une identité diasporique mondiale liée à la libre circulation des capitaux. En utilisant l'argent comme un substitut pour les documents d'identité, les réfugiés ont fait appel à une notion de droits autonome à l'état.